AUTOIMMUNE POLYGLANDULAR SYNDROME TYPE II IN A PATIENT PRESENTING WITH GYNAECOLOGICAL SYMPTOM: A CASE REPORT - PS, Wong; LS, Yong; R, Surenthiran; CK, Er; S, Sharifah; K, Nor Afidah; A, Noor Lita (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Autoimmune polyglandular syndromes (APS) are rare endocrinopathies characterized by the coexistence of at least two endocrine gland insufficiencies that are based on autoimmune mechanisms. We report a 45-year-old lady who was diagnosed as APS-2 following a presentation of menorrhagia. CASE A 45-year-old lady with underlying primary hypothyroidism on thyroxine replacement, presented with menorrhagia. Further history revealed significant weight loss, lethargy, loss of appetite, alopecia and skin darkening over the ears. On examination, blood pressure was 110/59 mmHg, hyperpigmentation was found at buccal mucosa, palmar creases, trunks and extremities. Gynaecological assessment revealed no abnormalities. Initial blood investigations showed pancytopenia, normal electrolytes and normal thyroid function test. She was treated as symptomatic anaemia secondary to abnormal uterine bleeding and received blood transfusion. Subsequently, she became confused, disoriented and had pre-syncopal attack. The clinical suspicion of Addison’s disease was raised after review of her clinical profile. The raised ACTH (260.0 pmol/L) and short synacthen test (0 min cortisol 69.4 nmol/L, 30 minutes 78.2 nmol/L, 60 minutes 69.8 nmol/L) confirmed the suspicion of primary adrenal insufficiency. Serum Dehydroepiandrosterone sulphate was <0.14 umol/L. Plasma aldosterone and renin was sent concurrently. Patient had mixed iron and vitamin B12 deficiency and was treated accordingly. The aetiology of the primary adrenal insufficiency was postulated to be autoimmune origin. Further evaluation including Computer tomography of the adrenal glands; anti-parietal cell antibodies and anti- 21-OH antibodies were planned. Patient showed marked improvement in symptoms after initiation of hydrocortisone replacement and discharged in stable condition. CONCLUSION This case highlights the significance of a timely diagnosis and appropriate treatment of APS-2. Physicians need to sharpen their awareness of the potentially serious and lifethreatening consequences.